Attitude of Military and Paramilitary Officers towards the Role of Arabic Language in Addressing Security Issues in Nigeria - Abdullahi, Musa Siddiq; Musa Salisu (IIUM Journal of Educational Studies, 2019)
This study addresses security issues in Nigeria through Arabic Language Education. Arabic Language is one out of the international languages, it is a member of the Semitic family of language and perhaps the only one among them that has gallantly stood the test of the time. It gains wide range of currency and leaves an indelible mark on the course of world history, culture and civilization. The language has played a significant role in security challenges. It has the ability to solve problems between groups of people by ensuring atmosphere for understanding and peaceful co-existence. The study was a descriptive survey type. The population consisted of all Nigerian military and paramilitary officers using stratified random sampling technique, 50 officers were selected from each of the Nigerian Army, Air force, Police, and Civil Defence corps in the North-east totaling 200. A questionnaire titled “Arabic Language Education and National Security Questionnaire” was designed for the data collection. Test re-test method was employed for the reliability with 0.76 coefficient. One research question and one hypothesis guided the study. Percentage was used to answer the research question and ANOVA was used to test the hypothesis at 0.05significance level. The findings reveal that there was a significant difference in the understanding of Arabic Language among Nigerian security officers. Significant difference was found in addressing insecurity through Arabic than in other languages. It was recommended among others that, the government should recognize Arabic Language as a medium of communication/instruction and of the equal rank with English language in Nigeria. The Language should be incorporated into in-house training for the security officers. Keywords: Nigeria, Security, Arabic Language, Role